TENSION PNEUMOPERITONEUM: A RARE PRESENTATION OF MEGACYSTIS MICROCOLON INTESTINAL HYPOPERISTALSIS SYNDROME - Raza, Farheen; Jehangir, Maham; Nazir, Rashed; Khan, Nasir Aziz (Journal of Ayub Medical College Abbottabad, 2018)
Megacystis microcolon intestinal hypoperistalsis syndrome (MMIHS) also known as Berdon syndrome is a rare autosomal recessive disorder characterized by enlarged urinary bladder, small colon and reduced or absent intestinal peristalsis. We report a case of a 4 days old female presenting with tension pneumoperitoneum. She underwent emergent decompression of the pneumoperitoneum followed by laparotomy which showed a sigmoid perforation. Her per-operative findings, antenatal and postanatal imaging were consistent with a diagnosis of MMIHS. She was treated with a palliative colostomy, vesicostomy and parenteral nutrition. To the best of our knowledge, this is the first reported case of Berdon syndrome presenting atypically with tension pneumoperitoneum. Megacystis microcolon intestinal hypoperistalsis syndrome also known as Berdon syndrome is characterized by enlarged urinary bladder, small colon and reduced or absent intestinal peristalsis. We report a case of 4 days old female suffering from MMIHS presenting with tension pneumoperitoneum. To the best of our knowledge, this is the first reported case of MMIHS, having this unusual presentation. Keywords: Tension pneumoperitoneum; megacystic microcolon; Intestinal hypoperistalsis; syndrome; perforation; Intestinal malrotation